2016
DOI: 10.1007/s00590-016-1797-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical outcomes between fixation with hook plate and loop suspensory fixation for acute unstable acromioclavicular joint dislocation: a systematic review and meta-analysis

Abstract: Treatment of acute (≤4 weeks) high-grade acromioclavicular (AC) joint separation (types III-VI) is still controversial. Currently, the two modern techniques that are widely used include hook plate fixation and coracoclavicular (CC) ligament fixation using a suspensory loop device (tightrope, synthetic ligament or absorbable polydioxansulfate sling). These techniques are both reported to have superior clinical outcomes. This systematic review and meta-analysis aimed to assess and compare clinical outcomes of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 32 publications
1
17
0
2
Order By: Relevance
“…In this study, group II demonstrated a signi cantly shorter surgical duration and less blood loss as compared with group I (101.0 ± 38.0 vs 66.6 ± 26.1 minutes, p = 0.005; 17.5 ± 25.6 vs 43.8 ± 45.6 ml, p = 0.015). The result was compatible with a systemic review and meta-analysis by Alisara et al [25], which indicated that hook plate xation required a signi cantly shorter surgical duration than loop suspensory…”
Section: Discussionsupporting
confidence: 90%
“…In this study, group II demonstrated a signi cantly shorter surgical duration and less blood loss as compared with group I (101.0 ± 38.0 vs 66.6 ± 26.1 minutes, p = 0.005; 17.5 ± 25.6 vs 43.8 ± 45.6 ml, p = 0.015). The result was compatible with a systemic review and meta-analysis by Alisara et al [25], which indicated that hook plate xation required a signi cantly shorter surgical duration than loop suspensory…”
Section: Discussionsupporting
confidence: 90%
“…Many surgical methods have been developed over decades and there still exists a problem concerning the optimal operative treatment between internal fixation or reconstruction of CC ligaments, both of which have their pros and cons 6 . For CC ligaments reconstruction, non-absorbable suture, allogenous/autogenous tendons and the flip-button techniques such as Tightrope system (Arthrex Inc, Naples, FL, USA) and Endobutton system (Smith&Nephew Inc, Memphis, TN, USA) have been widely used [7][8][9][10][11] .…”
mentioning
confidence: 99%
“…Оценивая биомеханические свойства приме-няемых фиксаторов, коллектив ортопедов из Гер-мании провёл исследование в лабораторных усло-виях особенностей нативного АКС по сравнению с АКС после хирургического восстановления тремя разными методами фиксации: крючковидной плас-тиной, «TightRope» и якорным фиксатором [13]. Для того чтобы выяснить, какой имплантат имитирует физиологические свойства сустава лучше всего, была оценена осевая жёсткость при вертикальной стабильности в сочетании с ротацией.…”
Section: обмен клиническим опытомunclassified
“…После изучения «биомеханического анализа трёх способов стабилизации АКС», проведённо-го коллективом авторов из Германии [13], воз-никла другая гипотеза, согласно которой нельзя исключить недостаточность фиксации одной системой (две пуговицы и одна нить), предот-вращающей смещение (вывих) только в одной плоскости. Возможно, что при использовании систем типа «Double TightRope», где фиксацию выполняют тремя пуговицами и двумя нитями, проводимыми через три костных «точки», дан-ного осложнения можно было бы избежать.…”
Section: обмен клиническим опытомunclassified